2016
DOI: 10.1186/s40249-016-0180-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with changes in uptake of HIV testing among young women (aged 15–24) in Tanzania from 2003 to 2012

Abstract: BackgroundThis study explored the factors associated with changes in HIV testing uptake among young women in Tanzania, based on an analysis of data from the 2003–2004 Tanzania HIV/AIDS Indicator Survey, and the 2007–2008 and 2011–2012 Tanzania HIV/AIDS and Malaria Indicator Surveys.MethodsThe study population consisted of young women aged 15–24 years at the time of the survey. Multivariate decomposition analysis was used to assess factors associated with changes in HIV testing uptake between the 2003–2004 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 28 publications
16
44
0
Order By: Relevance
“…The same observation had been made by other studies. Adolescents are less likely to use HIV testing services (8,14,(20)(21)(22)(23). Several explanations can be advanced.…”
Section: Discussionmentioning
confidence: 99%
“…The same observation had been made by other studies. Adolescents are less likely to use HIV testing services (8,14,(20)(21)(22)(23). Several explanations can be advanced.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with other findings namely in Sierra Leone (Brima et. al 2015), Tanzania (Mahande et. al 2015) Italy (Renzi et.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from other sub-Saharan African countries such as Tanzania [5] Congo, Mozambique, Uganda [6] and Ethiopia [7] have indicated that educated pregnant women are likely to fully utilise HIV Testing and Counselling (HTC) service compared to women who are not educated. Mahande et al [5] explained that higher education offers a better understanding of HIV infection and prevention and as a result may increase the possibility of utilising the full continuum of HTC service. In the case of Ghana, no national-level empirical study has been undertaken to determine whether the level of education contributes to getting results for HTC at ANC or otherwise.…”
Section: Introductionmentioning
confidence: 99%